The Role of Gut Microbiota in Human Health and Disease - Wahid Suwadi, Zahraa Manfi; Lafta Zamel, Zahraa Adnan; Lafta Zamel, Yasmine Adnan; Hasan Alramadan, Saja Abdulkareem; Abdul-Hassan Omran, Furqan Aamer (American Journal of Biology and Natural Sciences, 2025)
The human gut microbiome is the focus of intensifying scientific investigations. Several large-scale projects have been initiated, including but not limited to the Western simplifying Human Microbiome Project (HMP) and the European Union Metagenomics of the Human Intestinal Tract (MetaHIT). These large-scale endeavors both share similar missions in characterizing the human microbiome and their roles in health and disease states, with MetaHIT solely focusing on the gut microbiome. There are several analyses have been incorporated in these meta-omics projects including (1) 16S ribosomal RNA (rRNA) sequencing to taxonomically characterize the microbiota communities (2) Whole Genome Shotgun (WGS) metagenomic sequencing of body-site specific whole community DNA, followed by reference genome mapping, metagenomic assembly, gene cataloging and metabolic reconstruction, to facilitate maximal capture of organismal and functional data of the human microbiota. Due to the inherent complexity and heterogeneity of the human microbiome, several experimental models have been launched (all following the Western simplifying HMP criteria) where gnotobiotic animals are colonized with simplified, known consortium of bacterial strains (a model of the human microbiome). These new “simpler” model animals will prospectively exhibit divergent health conditions (ranging from obese to metabolic syndrome to IBD), illustrating the causation links between particular microbiota community members or gene functions and these health silences. This knowledge is expected to open up new avenues for future therapeutic approaches for reshaping an ensemble of human associated microbial communities and their genetic functions to confer or restore good health [1]. The symbiotic relationship between the gut microbiota and the host is regulated and stabilized by a complex network of interactions that encompass metabolic, immune, and neuroendocrine crosstalk between them, and it has been proposed to physiologically link the gut with several health conditions, including the CNS, the immune system, and the endocrine system. Chronic diseases such as obesity, metabolic syndrome, mood disorders, and immunological dysregulations are postulated to at least in part derive from bi-direction aberrant communication routes between the GIT and these organs due to conditions such as high fat diet, chronic psychological stress, infection, or chronic use of antibiotics. These conditions can potentially alter the complex mutually beneficial relationship between the gut microbiota and the host, resulting in disturbances of the microbial population and the possible occurrence of dysbiotic health conditions.